Role of Microvascular Disruption in Brain Damage from Traumatic Brain Injury. Issue 3 (24th June 2015) - Logsdon, Aric F.; Lucke‐Wold, Brandon P.; Turner, Ryan C.; Huber, Jason D.; Rosen, Charles L.; Simpkins, James W.
ABSTRACT: Traumatic brain injury (TBI) is acquired from an external force, which can inflict devastating effects to the brain vasculature and neighboring neuronal cells. Disruption of vasculature is a primary effect that can lead to a host of secondary injury cascades. The primary effects of TBI are rapidly occurring while secondary effects can be activated at later time points and may be more amenable to targeting. Primary effects of TBI include diffuse axonal shearing, changes in blood‐brain barrier (BBB) permeability, and brain contusions. These mechanical events, especially changes to the BBB, can induce calcium perturbations within brain cells producing secondary effects, which include cellular stress, inflammation, and apoptosis. These secondary effects can be potentially targeted to preserve the tissue surviving the initial impact of TBI. In the past, TBI research had focused on neurons without any regard for glial cells and the cerebrovasculature. Now a greater emphasis is being placed on the vasculature and the neurovascular unit following TBI. A paradigm shift in the importance of the vascular response to injury has opened new avenues of drug‐treatment strategies for TBI. However, a connection between the vascular response to TBI and the development of chronic disease has yet to be elucidated. Long‐term cognitive deficits are common amongst those sustaining severe or multiple mild TBIs. Understanding the mechanisms of cellular responses following TBI is important to prevent the development of neuropsychiatric symptoms. With appropriate intervention following TBI, the vascular network can perhaps be maintained and the cellular repair process possibly improved to aid in the recovery of cellular homeostasis. © 2015 American Physiological Society. Compr Physiol 5:1147‐1160, 2015.